Fun meets learning: Karnival Digital STEMria JJ MADANI peringkat Negeri Sembilan - Mohd Ruslan, Siti Zaharah; Othman, Norlida; Yaacob, Nurul Aityqah; Tuan Zakaria, Tuan Norhafizah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Karnival Digital STEMria JJ MADANI Peringkat Negeri Sembilan was held on 20 August 2025 at Kompleks Rakan Muda Bandar Seri Jempol and organised by Pejabat Pendidikan Daerah Jempol Jelebu. UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah participated by setting up a booth featuring the Faculty of Computer and Mathematical Sciences, along with the Physics and Biology departments from the Faculty of Applied Sciences. The event engaged primary and secondary school students from the Jempol and Jelebu districts through interactive STEM activities and academic outreach.